Modulate Molecular Interaction between Hole Extraction Polymers and Lead Ions toward Hysteresis‐Free and Efficient Perovskite Solar Cells. Issue 15 (5th June 2018) - Zhang, Zhongqiang; Fu, Weifei; Ding, Honghe; Ju, Huan‐Xin; Yan, Kangrong; Zhang, Xinqian; Ding, Feizhi; Li, Chang‐Zhi; Chen, Hongzheng
Abstract: Herein three polymeric hole extraction materials (HEMs), poly(benzene‐dithiophene) (PB2T)‐O, PB2T‐S, and PB2T‐SO are presented for p–i–n perovskite solar cells (PVSCs). This study reveals that the perovskite device hysteresis and performance heavily rely on the perovskite grain boundary conditions. More specifically, they are predetermined through the molecular interaction between Lewis base atoms of HEMs and perovskites. It is revealed that only changing the side chain terminals (OCH3, SCH3, and SOCH3 ) of HEMs results in effective modulating PVSC performance and hysteresis, due to the effective tune of interaction strength between HEM and perovskite. With an in situ grown perovskite‐HEM bulk heterojunction structure, PB2T‐O with weak binding group (OCH3, −78.9 kcal mol −1 bonding energy) to lead ions allows delivering hysteresis‐free and efficient devices, which is sharp contrast to the strong binding PB2T‐SO (−119.3 kcal mol −1 bonding energy). Overall, this work provides new insights on PVSC hysteresis and the related curing methods via multifunctional HEM design in PVSCs. Abstract : Three polymeric hole extraction materials are developed for p–i–n perovskite solar cells. It reveals that the side chain terminals can largely influence the resultant device performance and hysteresis, due to the different interaction between hole extraction material (HEM) and perovskite. An effective perovskite‐HEM heterojunction, facilitating hole‐collection and surface passivation, is realized in situ during fabrication.